Iconography of the Literary Look: An Ovidian Interpretation of the So-Called Nilotic Mosaic of Merida (No. 9 of the Corpus of MRH-MRM) - García-Manso, Angélica; Tovar Paz, Francisco Javier (Eikón / Imago, 2024)
The so-called Nilotic Mosaic of Mérida (no. 9 in the MRH-MRM corpus) was found in the mid-19th century. The extraordinary nature of its design was evident from the moment it was found, although, unfortunately, popular superstition largely destroyed the pavement, but not before a draft of its contents was drawn, and numerous remains were preserved, so that it has been reconstructed and is on display in the National Museum of Roman Art in Mérida (Extremadura - Spain). The mosaic combines exotic, cultural and annual cycle elements, but no overall interpretation of the mosaic has yet been postulated. However, it seems possible to make an integrative reading based on the myth of the contest between the Muses and the Pyerides from the Ovidian Metamorphoses. Such a reading gives unity to the amalgam of iconographic motifs and may even explain the choice of a predominantly dichromatic technique in keeping with the colours of the magpies into which the Pyerides were transformed and also in keeping with a precept of literary creation that warns against hybris.